Receptor Tyrosine Kinase Ephb6 Regulates Vascular Smooth Muscle Contractility and Modulates Blood Pressure in Concert with Sex Hormones - Luo, Hongyu (American Society for Biochemistry and Molecular Biology, 2012)
Eph kinases constitute the largest receptor tyrosine kinase family, and their ligands, ephrins (Efns), are also cell surface molecules. Our study is the first to assess the role of Ephb6 in blood pressure (BP) regulation. We observed that EphB6 and all three of its Efnb ligands were expressed on vascular smooth muscle cells (VSMC) in mice. We discovered that small arteries from castrated Ephb6 gene KO males showed increased contractility, RhoA activation, and constitutive myosin light chain phosphorylation ex vivo compared with their WT counterparts. Consistent with this finding, castrated Ephb6 KO mice presented heightened BP compared with castrated WT controls. In vitro experiments in VSMC revealed that cross-linking Efnbs but not Ephb6 resulted in reduced VSMC contractions, suggesting that reverse signaling through Efnbs was responsible for the observed BP phenotype. The reverse signaling was mediated by an adaptor protein Grip1. Additional experiments demonstrated decreased 24-h urine catecholamines in male Ephb6 KO mice, probably as a compensatory feedback mechanism to keep their BP in the normal range. After castration, however, such compensation was abolished in Ephb6 KO mice and was likely the reason why BP increased overtly in these animals. It suggests that Ephb6 has a target in the nervous/endocrine system in addition to VSMC, regulating a testosterone-dependent catecholamine compensatory mechanism. Our study discloses that Ephs and Efns, in concert with testosterone, play a critical role in regulating small artery contractility and BP.